Calidad del servicio y competitividad del Multicentro Arica SAC sección ferretería 2024 - Del Aguila del Aguila, Harold (2025)
The objective of this research study was to determine the relationship between the quality of service and competitiveness of Multicentro Arica SAC hardware section 2024. A basic study was chosen, using a descriptive correlational approach and a non-experimental design. The sample consisted of 84 clients of the company, and data collection was carried out using the survey and questionnaire technique as instruments. The results obtained indicate that the quality of service offered by Multicentro Arica SAC in its hardware section is considered high by 46%. This is because customers consider that the customer service staff is almost always friendly and cordial. However, 61% indicate that sometimes the staff offers their help promptly and efficiently. Regarding the level of competitiveness of Multicentro Arica SAC, it is highlighted that 33% consider it high. This is because the company almost always offers innovative products compared to other hardware stores. However, 68% say that they sometimes see continuous improvements in existing products or services. Therefore, we can deduce that there is a significant relationship between service quality and competitiveness of Multicentro Arica SAC, demonstrated by a coefficient of 0.733 and a bilateral significance of 0.000, which means that it is lower than the previously established significance level of 0.01.